2010
DOI: 10.1124/jpet.110.172130
|View full text |Cite
|
Sign up to set email alerts
|

The Residual Nonadrenergic Contractile Response to Nerve Stimulation of the Mouse Prostate Is Mediated by Acetylcholine but Not ATP in a Comparison with the Mouse Vas Deferens

Abstract: Neuronal release of noradrenaline is primarily responsible for the contraction of prostatic smooth muscle in all species, and this forms the basis for the use of ␣ 1 -adrenoceptor antagonists as pharmacotherapies for benign prostatic hyperplasia. Previous studies in mice have demonstrated that a residual nonadrenergic component to nerve stimulation remains after ␣ 1 -adrenoceptor antagonism. In the guinea pig and rat prostate and the vas deferens of guinea pigs, rats, and mice, ATP is the mediator of this resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 38 publications
2
19
2
1
Order By: Relevance
“…The decrease in the potency of acetylcholine observed in prostates taken from M 3 muscarinic receptor heterozygous mice may be a product of fewer M 3 muscarinic receptors being available, whereas the response to acetylcholine in prostates taken from M3R(ϩ/ϩ) mice was comparable with our previous results (White et al, 2010). The absence of a contractile response to acetylcholine, except at high concentrations (as discussed previously) in M3R(Ϫ/Ϫ) mice, further confirms the M 3 muscarinic receptor as the subtype mediating contraction in the mouse prostate gland.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The decrease in the potency of acetylcholine observed in prostates taken from M 3 muscarinic receptor heterozygous mice may be a product of fewer M 3 muscarinic receptors being available, whereas the response to acetylcholine in prostates taken from M3R(ϩ/ϩ) mice was comparable with our previous results (White et al, 2010). The absence of a contractile response to acetylcholine, except at high concentrations (as discussed previously) in M3R(Ϫ/Ϫ) mice, further confirms the M 3 muscarinic receptor as the subtype mediating contraction in the mouse prostate gland.…”
Section: Discussionsupporting
confidence: 80%
“…However, this seems unlikely in the prostate because the residual contractile response to electrical-field stimulation in prostates taken from M3R(Ϫ/Ϫ) mice is abolished by the ␣ 1 -adrenoceptor antagonist prazosin. Furthermore this confirms that the nerve-mediated contractile response in the mouse prostate is mediated by both muscarinic receptors and ␣ 1L -adrenoceptors (White et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Isolated organ bath experiments were conducted as described (25,26). Intracellular electrical recordings of vas deferens smooth muscle were as described (15).…”
Section: Generation Of Doublementioning
confidence: 99%
“…For example, some studies showed that electric field stimulation (EFS)-evoked contractions of the vas deferens were inhibited by the muscarinic receptor (MR) antagonist atropine (Fukushi and Wakui 1986; White et al. 2010) whereas as others showed that atropine had little, or no effect (Nakanishi et al. 2004; Cuprian et al.…”
Section: Introductionmentioning
confidence: 93%